2019
DOI: 10.1098/rsta.2019.0091
|View full text |Cite
|
Sign up to set email alerts
|

Primordial black holes and the origin of the matter–antimatter asymmetry

Abstract: We review here a new scenario of hot spot electroweak baryogenesis where the local energy released in the gravitational collapse to form primordial black holes (PBHs) at the quark-hadron (QCD) epoch drives over-the-barrier sphaleron transitions in a far from equilibrium environment with just the standard model CP violation. Baryons are efficiently produced in relativistic collisions around the black holes and soon redistribute to the rest of the universe, generating the observed matter–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 64 publications
0
17
0
1
Order By: Relevance
“…In either case, it has been found that a PBHs mass spectrum spanning a few orders of magnitude in the range of O(0.01 − 1000) which for any particular mass does not reach more than 40% of the DM energy density is still viable (see in [15,20,36,70,71]).…”
Section: Observational Constraintsmentioning
confidence: 99%
“…In either case, it has been found that a PBHs mass spectrum spanning a few orders of magnitude in the range of O(0.01 − 1000) which for any particular mass does not reach more than 40% of the DM energy density is still viable (see in [15,20,36,70,71]).…”
Section: Observational Constraintsmentioning
confidence: 99%
“…In either case it has been found that a PBHs mass spectrum spanning a few orders of magnitude in the range of O(0.01 − 1000) which for any particular mass does not reach more than 40% of the DM energy density is still viable (see Refs. [15,20,35,69,70]).…”
Section: B Observational Constraintsmentioning
confidence: 99%
“…Following the predictions in [1] I make the simplifying assumption that all dark matter exists in the form of 1.4 M black holes, created seconds after the Big Bang. As we will see, for most of the cosmic history these black holes move at supersonic speeds among the baryons and will therefore undergo Bondi-Hoyle-Lyttleton quasi-spherical accretion [30][31][32].…”
Section: Basic Parameters Of the Toy Modelmentioning
confidence: 99%
“…In a recently published theoretical prediction [1,9] PBH are created in the QCD phase transitions (around 100 MeV) of different particle families freezing out of the primordial Quark-gluon plasma within the first two seconds after the inflationary phase. When W +/− , Z bosons, baryons, pions are created, and e + e − pairs annihilate, they leave an imprint in form of a significant reduction of the sound speed at the corresponding phase transitions, and allow regions of high curvature to collapse and form PBH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation